VOLUNTEERING AS A MEANS OF SELF-DETERMINATION AND SELF-REALISATION OF YOUTH - Marchuk, Alla; Loboda, Victoria; Ivanysa, Vasylyna (Socio-economic relations in the digital society, 2023)
The paper dwells upon and analyses the place and role of volunteering in the self-determination and self-realisation of today’s youth, as well as the phenomenon of volunteering in scientific research conducted by foreign and Ukrainian scientists is analysed. The main characteristics and potential opportunities for volunteering are revealed, and the important aspects of self-determination and self-realisation of youth in volunteer activities are described. The paper substantiates the role of volunteering in the development of the personality of a young person, and the formation of his/her important personal qualities and needs, which affect his/her ability to self-realisation and self-determination. It is proven that volunteering has significant potential for developing independence, autonomy, flexibility, sensitivity, and other important traits of personality that contribute to the self-realisation and self-determination of young people. It is noted that young people who are actively involved in the volunteer movement respect themselves and others, accept themselves as they are, understand other people quite well; and they have a more optimistic outlook of the world and of themselves in it. The presented study is conditioned by the problematic situation and emergency conditions in Ukraine, which have significantly influenced and sometimes complicated the processes of self-realisation and self-determination of today’s youth. The paper reveals the potential of volunteer activities for self-realisation and self-determination of young people.
Keywords: volunteering; volunteer activities; social activity; self-determination; self-realisation